Agricultural and Environmental Research in Small Countries: Innovative Approaches to Strategic Planning - Eyzaguirre, Pablo B. (International Service for National Agricultural Research, 1996)
Developing countries are finding it increasingly difficult to maintain research institutions that can support the broad demands of their agricultural and natural resource sectors. In many countries, this is due to a diminutive economy and population which limits the resource base upon which to build a viable, productive research system. This book examines the ways small countries have approached these problems and how they can use their small-scale institutions and limited resources to best advantage. The main feature of this book is a national portfolio approach to the strategic planning of research. This approach addresses the many institutional, policy, and scientific demands that stretch the scope of research in small developing countries, including new developments in natural resource management, biotechnology, regional collaboration, networking, and the management of scientific information. Based on the experience of small countries with small research organisations, Agricultural and Environmental Research in Small Countries provides valuable lessons for all policymakers and scientific leaders who are looking for innovative ways to address the growing complexity of national agricultural research in the emerging global system.